THE INFLUENCE OF BUDGETARY PLANNING, BUDGET CLARITY, REPORTING STRUCTURES, AN D INTERNAL CONTROL SYSTEMS IN PERFORMANCE ACCOUNTABILITY - Ester Salsanabila Jipa; Ratih Kusumastuti (Adisam Publisher, 2024)
Using the internal control system of the Jambi Provincial Regency Government as a moderating variable, this study examines the effects of budget planning, target accuracy, and reporting systems on the accountability of regional government performance. 42 respondents participated in the descriptive-quantitative study, which was carried out at the Jambi Financial Agency using a saturated sample method. Both multiple linear regression and moderated regression analysis (MRA) are used in the analysis. The findings show that performance accountability is highly impacted by reporting systems, budget planning, and well defined budget objectives. The effect of reporting systems and budget objectives being clear on performance responsibility is mitigated by the internal control system. It does not, however, lessen the connection between performance responsibility and budget planning.